COMBUSTION MODELING OF GASOLINE TWO-STROKE LINEAR ENGINE BY THE MODIFIED WEIBE FUNCTION - Tulus et al. (Proceedings of ICMSA, 2005)
This paper presents the mathematical modeling of combustion in a two-strokelinear combustion engine incorporating combustion and kickbackchambers. A thermodynamics simulation is performed using a Weibeflrnction that applied to linear engine. The computer program isdeveloped to compute the instantaneous velocity and temperature in thecombustion chamber. The fuel is gasoline and the cylinder bore sizes tobe considered are of 50mm and 76mm. From the computation, theresults show that the peak temperatures are 870 K and 995 K, the meanvelocities during expansion are 3.8m/s and 5m/s, the mean velocitiesduring compression 2.9m/s and 4.4m/s, respectively.Keywords: mathematical modeling combustiorl linear engine